Effect of various inhibitors on the multiplication of BLE bacteriophage in Bacillus licheniformis - Lipavská, H; Rytír, V; Vanĕk, Z; Steinerová, N; Bĕlík, E (Folia microbiologica, 1978)
A total of 40 substances were tested for their inhibitory effect on the multiplication of a bacteriophage in a growing culture of Bacillus licheniformis and their influence on bacitracin production. Acriflavine was the only substance which, at a concentration of 3 microgram ml-1, completely suppressed phage multiplication while having no effect on the growth of Bacillus licheniformis and on the production of the antibiotic.
Keywords: Virus Replication; akriflavin; bacitracin; Bacillus; Anti-Infective Agents; Bacitracin; antiinfekční látky; bakteriofágy; Anti-Bacterial Agents; Bacteriophages; antibakteriální látky; Acriflavine; replikace viru